A Typology of Family Functioning at The Beginning of The COVID-19 Pandemic - Firdanianty Pramono (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
Family functioning affects the physical and psychological health of individuals in the family. The more effortlessly a family performs its various functions, the better the mental health of its members. The purpose of this research is to analyze family issues and explore the elements that influence family functioning following the implementation of the Large Scale Social Restrictions (PSBB) policy. The research was conducted using an online survey method via Google form application. Data were collected from 18 provinces, with West Java having the highest percentage (54.8%), followed by DKI Jakarta (12.3%), Riau (7.1%), East Java (6.5%), and South Sumatra (6.0%). Data were processed using SPSS version 20, followed by descriptive and regression analysis. Based on the dimensions of family functioning, the results showed that more than 80 percent of the aspects of communication and affective responsiveness were in the low category. In comparison, more than 90 percent of responders rate their role and behavioral control as high. According to the functioning typology, as many as 64% of families have less functioning conditions, while 36% of families are still functioning well. According to the findings, the COVID-19 epidemic has also caused additional challenges for families, especially children (63.5%) and economic problems (49.5%). These findings are intended to provide useful information to the government and academia in strengthening family resilience during times of crisis.